2015
DOI: 10.1016/j.watres.2015.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Algal remediation of CO2 and nutrient discharges: A review

Abstract: The recent literature pertaining to the application of algal photobioreactors (PBRs) to both carbon dioxide mitigation and nutrient abatement is reviewed and the reported data analysed. The review appraises the influence of key system parameters on performance with reference to (a) the absorption and biological fixation of CO2 from gaseous effluent streams, and (b) the removal of nutrients from wastewaters. Key parameters appraised individually with reference to CO2 removal comprise algal speciation, light int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 93 publications
(96 reference statements)
1
74
0
Order By: Relevance
“…In spring, factors including the appropriate temperatures, slow flow velocity due to scarce rainfall, and nutrients enrichment due to point and nonpoint sources led to algal blooms in many tributaries of the Yangtze River, especially after the construction of the Three Gorges Reservoir [ Cao et al ., ; Da et al ., ], decreasing the water p CO 2 . The capture, utilization, and storage of CO 2 by algae in water can draw down the p CO 2 in eutrophic rivers [ Judd et al ., ]. Our investigation showed that the river water p CO 2 was probably influenced at the same time by the dilution effect of persistent rainfall and biogenic CO 2 uptake; however, which mechanism was dominant depends on the rainfall intensity and temperature.…”
Section: Discussionmentioning
confidence: 69%
“…In spring, factors including the appropriate temperatures, slow flow velocity due to scarce rainfall, and nutrients enrichment due to point and nonpoint sources led to algal blooms in many tributaries of the Yangtze River, especially after the construction of the Three Gorges Reservoir [ Cao et al ., ; Da et al ., ], decreasing the water p CO 2 . The capture, utilization, and storage of CO 2 by algae in water can draw down the p CO 2 in eutrophic rivers [ Judd et al ., ]. Our investigation showed that the river water p CO 2 was probably influenced at the same time by the dilution effect of persistent rainfall and biogenic CO 2 uptake; however, which mechanism was dominant depends on the rainfall intensity and temperature.…”
Section: Discussionmentioning
confidence: 69%
“…CO 2 fixation as a function of I appears to follow no recognisable pattern across either different species or different investigations for the same species . Against this, for individual studies subject to the same standardized conditions fixation and biomass productivity both increase with I as expected to some maximum governed by light saturation .…”
Section: Introductionmentioning
confidence: 82%
“…Microalgae, configured as photobioreactors (PBRs), has attracted considerable attention as the basis of combined biological method for removal of nutrients (nitrogen N and phosphorus P) from wastewaters and CO 2 fixation from flue gases . The microalgae Chlorella vulgaris has been extensively studied for CO 2 mitigation under a range of operating conditions, including gas CO 2 concentration, light intensity and temperature .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations